ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s)
News on various topics, including Liberia's first female presidential candidate (Ms. Danquah); and loan agreement of Liberia Electricity Corporation (LEC).
Keywords: News; Public Affairs